2003
DOI: 10.1155/2003/792917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Positive End‐Expiratory Pressure on Oscillated Volume during High‐Frequency Chest Compression in Children with Cystic Fibrosis

Abstract: OBJECTIVE:To investigate the effects of positive end-expiratory pressure (PEEP) on end-expiratory lung volume (EELV) and mean oscillated volume (V osc ) during high frequency chest compression (HFCC). DESIGN: A clinic-based prospective intervention study. SETTING: Pulmonary function laboratory, University of Alberta, Edmonton, Alberta. POPULATION: Nine children with cystic fibrosis with little or no obstructive airway disease who were selected from the outpatient Cystic Fibrosis and Pediatric Pulmonary Clinics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Guerin et al (45) indicated that inspiratory airway resistance decreased with increasing lung volume from positive end-expiratory pressure. In 2003, Dosman et al (47) found that the addition of a small amount of positive end-expiratory pressure (2.0±0.3 cm H 2 O) during HFCC prevented the HFCC-induced decrease in endexpiratory lung volume and significantly increased the mean oscillated volume during expiration in pediatric patients with cystic fibrosis.…”
Section: Effects Of Positive End-expiratory Pressure On Mucus Clearanmentioning
confidence: 99%
“…Guerin et al (45) indicated that inspiratory airway resistance decreased with increasing lung volume from positive end-expiratory pressure. In 2003, Dosman et al (47) found that the addition of a small amount of positive end-expiratory pressure (2.0±0.3 cm H 2 O) during HFCC prevented the HFCC-induced decrease in endexpiratory lung volume and significantly increased the mean oscillated volume during expiration in pediatric patients with cystic fibrosis.…”
Section: Effects Of Positive End-expiratory Pressure On Mucus Clearanmentioning
confidence: 99%
“…al (14) found that a small amount of PEP, between 2 cm H 2 O and 3.7 cm H 2 O, maintained EELV at the level of FRC and it increased mean oscillated volume measured at the mouth in pediatric patients with CF (12) and in older patients with chronic obstructive pulmonary disease (COPD) (14). It was concluded that decreases in airway resistance, due to the PEP-induced increase in EELV (15), accounted for the increases in oscillated volume.…”
Section: Original Articlementioning
confidence: 97%
“…HFCWO has been demonstrated to decrease end-expiratory lung volume (EELV) to as much as 50% of the functional residual capacity (FRC) in patients with airway disease (10) due to the increased load applied to the chest wall (11). The decreased EELV was found to have a secondary effect on decreasing the HFCWO-induced oscillated volume in humans (10,12) and in dogs (11,13), but this effect can be reversed with the use of positive expiratory pressure (PEP) in combination with HFCWO. Dosman et al (12) and Perry et ©2007 Pulsus Group Inc. All rights reserved…”
mentioning
confidence: 99%
“…50 Yuan y Dosman han empleado esta tecnología en pacientes pediátricos con problemas neurológicos (v.gr., parálisis cerebral y enfermedades neuromusculares); han informado un beneficio con menos fatiga y estancia hospitalaria con adecuada tolerancia. Otros escenarios clínicos están en proceso de ser analizados 51,52 (figura 4).…”
Section: Método De Oscilación De Alta Frecuenciaunclassified